2021
DOI: 10.1038/s41598-021-99206-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genome-wide analysis of WRKY, MADS-box and MYB transcription factor families in Arabidopsis and rice

Abstract: Transcription factors (TFs) form the major class of regulatory genes and play key roles in multiple plant stress responses. In most eukaryotic plants, transcription factor (TF) families (WRKY, MADS-box and MYB) activate unique cellular-level abiotic and biotic stress-responsive strategies, which are considered as key determinants for defense and developmental processes. Arabidopsis and rice are two important representative model systems for dicot and monocot plants, respectively. A comprehensive comparative st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 61 publications
1
22
0
Order By: Relevance
“…Analysis of cis -acting elements within the promoter region of the gene helps us to better understand the plant stress response. Studies showed that the light-responsive element G-box had the role of stress-responsive element, and the ABA-responsive element ABRE act as an important regulator of ABA-mediated stress response in plants ( Abdullah-Zawawi et al, 2021 ). Here, we found that the 2R-type IaMYB157 with abundant G-box and ABRE elements in its promoter region exhibited very strong response to Cd stress, indicating the possible function of IaMYB157 in plant response to Cd stress.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of cis -acting elements within the promoter region of the gene helps us to better understand the plant stress response. Studies showed that the light-responsive element G-box had the role of stress-responsive element, and the ABA-responsive element ABRE act as an important regulator of ABA-mediated stress response in plants ( Abdullah-Zawawi et al, 2021 ). Here, we found that the 2R-type IaMYB157 with abundant G-box and ABRE elements in its promoter region exhibited very strong response to Cd stress, indicating the possible function of IaMYB157 in plant response to Cd stress.…”
Section: Discussionmentioning
confidence: 99%
“…Among the additional interesting CDVd-responsive stem genes whose differential expression was verified by RT-qPCR (Figure 5A), several were found including the plant defense receptor-like protein 9DC3 (LOC102630240) [70]; the MADS-box transcription factor 23-like (LOC102630220) [71], which is part of the transcription factor (TF) families (WRKY, MADS-box and MYB) that activate unique abiotic and biotic stress-responsive strategies considered as key determinants for defense and developmental processes in most eukaryotic plants [72]; the phospholipase A1-Ibeta2 (LOC102609966) [73], the chloroplast import protein TIC 55 (LOC102614849), the chloroplast import protein [74]; the chloroplast pentatricopeptide repeat-containing protein ortholog of At1g08070 (LOC102619843), which is involved in RNA editing events within the chloroplast [75]; the transcription factor MYB13 (LOC102616893), which regulates meristem function by being a component of a regulatory network controlling the establishment and/or development of the shoot system in Arabidopsis [76]; protein IQ-DOMAIN 1, transcript variant X1 (LOC102628194) which plays a role with calmodulins or calmodulin-like proteins as well as involved in scaffolding in cellular signaling and trafficking [77,78]; hydroxyproline O-galactosyltransferase GALT3, transcript variant X3 (LOC102626136), which commits arabinogalactan proteins to the first step in arabinogalactan polysaccharide addition. AGP glycans play essential roles in both vegetative and reproductive plant growth [79]; cytochrome P450 82C4-like, which is involved in the early Fe deficiency response in Arabidopsis [80]; LOC102622795; thaumatinlike protein 1 (LOC102619709), involved in local responses of roots to colonization by non-pathogenic plant growth-promoting rhizobacteria [81].…”
Section: Discussionmentioning
confidence: 98%
“…The realization of these three main regulatory steps is inseparable from the role of various transcription factors. There are currently 58 transcription factor families in plants, many of which have numerous members and diverse functions, regulating multiple plant physiological processes; these include the MADS-box, MYB, NAC, and HD-Zip TF families [ 111 ]. Different transcription factors are involved in the above three main auxin regulatory steps, regulating various physiological processes of plant growth and development.…”
Section: Discussionmentioning
confidence: 99%